2008
DOI: 10.1088/0957-4484/19/33/335706
|View full text |Cite
|
Sign up to set email alerts
|

On the electronic and geometric structures of armchair GeC nanotubes: a hybrid density functional study

Abstract: Ab initio calculations within the framework of hybrid density functional theory and the finite cluster approximation have been performed for the electronic and geometric structures of three different types of armchair germanium carbide nanotube, from (3, 3) to (11, 11). Full geometry and spin optimizations with unrestricted symmetry have been performed. Physically pertinent quantities of interest such as the cohesive energies, band gaps, radial buckling, density of states, dipole moments, and Mulliken charge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 73 publications
2
44
0
Order By: Relevance
“…No differences of the Mulliken charge density as a function of length could be observed. As ionicity is believed to be responsible for the increasing localization of the electronic states [19], we observed higher localized HOMO and LUMO for larger diameter SiCNTs. However, orbitals localization also increased with length.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…No differences of the Mulliken charge density as a function of length could be observed. As ionicity is believed to be responsible for the increasing localization of the electronic states [19], we observed higher localized HOMO and LUMO for larger diameter SiCNTs. However, orbitals localization also increased with length.…”
Section: Resultsmentioning
confidence: 49%
“…(5,5), rises. This means that in general among armchair SiCNTs, the (2,2) are comparatively the least stable, because small diameter nanotubes have stronger curvature causing strain [19]. In fact, the (2,2) SiCNT has the broadest Si-C bond length distribution (1.76-1.87 Å) compared to the larger diameter ones (see Table 1), because the bonds expands to minimize the strain energy [19].…”
Section: Vac Homomentioning
confidence: 99%
“…Other applications of GeC thin films for design and preparation of durable multilayer coatings of infrared (IR) windows were reported in [13]. GeC nanotubes with an average diameter of 15 − 100nm were synthesized using MOCVD techniques as promising candidates for complex nano-based applications in wide band gap nanooptoelectronic devices and hydrogen storage [14,15]. In 2D, germanene/graphene hybrid is a honeycomb lattice where germanium and carbon atoms are arranged with sp 2 hybridization [16].…”
Section: Introductionmentioning
confidence: 99%
“…SiC nanotubes are also being successfully synthesized in various laboratories using various methods [26,27] and it has also been suggested that SiC nanotubes can be a potential candidate for hydrogen storage [28]. Rathi and Ray [29] studied the electronic and geometric structures of hydrogenated GeC nanotubes and found the nanotubes to be semiconducting.…”
Section: Introductionmentioning
confidence: 99%